Analysis of the Current Situation and Trends of Medical Translation Research in China - Zheng, Jie; Xiong, Lingsong; Luo, Ruifeng (International Journal of Membrane Science and Technology, 2023)
Medical translation is an interdisciplinary research direction between medicine and translation, with both theoretical and practical value. This study is based on the CNKI core paper database, utilizing the CiteSpace knowledge graph visualization tool and Excel data analysis. A systematic literature review method is used to sort out 1764 articles in Chinese medical translation related journals from 2001 to 2022, in order to clarify the research content and characteristics of medical translation. A dynamic econometric analysis was conducted on the current status and trends of medical translation research in the past two decades, and the results showed that: 1) Chinese medical translation research has shown an overall upward trend in the past two decades. 2) The research direction of influential authors in Chinese medical translation research is mostly traditional Chinese medicine translation, with research institutions mainly being universities of traditional Chinese medicine, and research achievements in Western medicine translation account for a relatively small proportion. 3) The main focus of Chinese medical translation research is the English translation of traditional Chinese medicine (TCM) terms. From the perspective of highlighted words, corpus and medical translation talent cultivation have been cutting-edge topics in recent years, and it is predicted that they will continue to grow in popularity in the future.